Experimental and numerical investigations of aluminium–steel self-piercing riveted joints under quasi-static and dynamic loadings. (December 2021) - Du, Zhanpeng; Wei, Baolv; He, Zhicheng; Cheng, Aiguo; Duan, Libin; Zhang, Guangya
Abstract: The mechanical response of aluminium–steelself-piercing riveted (SPR) joints is investigated under quasi-static and dynamic loadings using experimental and numerical methods separately. First, a 2D axisymmetric numerical model is constructed based on r -adaptivity method to simulate the SPR process and is subsequently validated by tests. Second, a novel generation method of 3D finite element (FE) model of SPR joints, of which the stress–strain field is mapped from the 2D axisymmetric model, is proposed to simulate the mechanical response of aluminium–steel​ SPR joints. The mechanical response of SPR joints under quasistatic and dynamic loadings are compared in detail by experimental tests and numerical simulation. The results reveal that the established 3D FE model can accurately simulate the quasi-static and dynamic strength of SPR joints. It is observed that the peak force of the SPR joints is larger under dynamic loading than under quasi-static loading; while the energy absorption by peeling and cross-tension SPR joints is lower under dynamic loading than quasistatic loading. Finally, the relationships between process parameters, process quality indexes and mechanical response of SPR joints are parametrically investigated under quasi-static and dynamic loadings, in which (1) increasing the rivet length reduces the minimum thickness, increases undercut, and increases energy absorption; (2) increasing the rivet length increases the peak force within a limited range for shear joints and cross-tension joints under dynamic loading; (3) the total effect of process parameters on the mechanical response of SPR joints under dynamic loading are similar to the effect observed under quasi-static loading. Highlights: A 2D numerical model is constructed to simulate the riveting process of SPR joints. A generation method of 3D FE model is proposed to simulate the SPR joints. The mechanical responses of SPR joints under dynamic loadings are investigated.